Creation and Evaluation of an Endodontic Diagnosis Training Software. (31st July 2020) - Al-Madi, Ebtissam M.; Al-Bahrani, Layla; Al-Shenaiber, Rafif; Al-Saleh, Samar A.; Al-Obaida, Mohammad I.
Abstract : Objective . The purpose of the study is to evaluate a user-friendly, comprehensive, fully integrated web- and mobile-based application that was specifically developed to guide learners and help them practice and train in pulpal and periapical diagnosis. Methods . The software was designed for assistance in the diagnosis of the pulpal and the periapical area. The software contained questions and tests, e.g., presence or absence of signs and symptoms, cold test, percussion, palpation, and radiographic examination that the user must answer to arrive at the final diagnosis. An electronic survey was prepared to evaluate the effectiveness, productivity, and accurateness of the software. The software and the electronic evaluation survey were sent by e-mail to dental students, endodontist, general dentists, and dental interns who study or work in four Saudi dental colleges. Data was analyzed using descriptive statistics. Result . A total of 203 questionnaires were completed. Results showed that 29% of the participants were highly satisfied with the software; 40% gave a very good rating about the application satisfaction, while only 2% reported a poor degree of satisfaction with the software. Results also showed that students accurately selected the correct diagnosis but received relatively low diagnostic proficiency scores because they did not request diagnostic data in a pattern similar to experts. Conclusion . In conclusion, the software is promising as an effective and efficient tool for teaching and assessing the diagnostic skills of learners.